Virtually Real, But Not Quite There: Social and Economic Barriers to Meeting Virtual Reality’s True Potential for Mental Health - Pimentel, Daniel; Foxman, Maxwell; Davis, Donna Z.; Markowitz, David M. (Frontiers in Virtual Reality, 2021)
Strategies to mitigate the spread of COVID-19, namely quarantine and social distancing protocols, have exposed a troubling paradox: mandated isolation meant to preserve well-being has inadvertently contributed to its decline. Prolonged isolation has been associated with widespread loneliness and diminished mental health, with effects compounded by limited face-to-face access to clinical and social support systems. While remote communication technologies (e.g., video chat) can connect individuals with healthcare providers and social networks, remote technologies might have limited effectiveness in clinical and social contexts. In this review, we articulate the promise of Virtual Reality as a conduit to clinical resources and social connection. Furthermore, we outline various social and economic factors limiting the virtual reality industry’s ability to maximize its potential to address mental health issues brought upon by the pandemic. These barriers are delineated across five dimensions: sociocultural, content, affordability, supply chain, and equitable design. After examining potential short- and long-term solutions to these hurdles, we outline potential avenues for applied and theoretical research seeking to validate these solutions. Through this evaluation we seek to (a) emphasize virtual reality’s capacity to improve mental health by connecting communities to clinical and social support systems, (b) identify socioeconomic barriers preventing users from accessing these systems through virtual reality, and (c) discuss solutions that ensure these systems can be equitably accessed via changes to existing and future virtual reality infrastructures.